2017
DOI: 10.1002/slct.201602029
|View full text |Cite
|
Sign up to set email alerts
|

Multimetallic Lithium Complexes Derived from the Acids Ph2C(X)CO2H (X=OH, NH2): Synthesis, Structure and Ring Opening Polymerization of Lactides and Lactones

Abstract: Reaction of LiOR (R=t‐Bu, Ph) with the acids 2,2/‐Ph2C(X)(CO2H), X=OH (benzH), NH2 (dpgH) was investigated. For benzH, one equivalent LiOt‐Bu in THF afforded [Li(benz)]2⋅2THF (1⋅2THF), which adopts a 1D chain structure. If acetonitrile is used (mild conditions), another polymorph of 1 is isolated; LiOPh also led to 1. Robust work‐up afforded [Li7(benz)7(MeCN)] 2MeCN THF (2⋅2MeCN⋅THF). Use of LiOt‐Bu (2 equivalents) led to {Li8(Ot‐Bu)2[(benz)](OCPh2CO2CPh2CO2t‐Bu)2(THF)4} (3), the core of which comprises two op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…The analytical HPLC was performed on a Gemini® 5 µm C18 110 Å LC column 150×4.6 mm (Phenomenex) at a flow rate of 1 mL min -1 , with a mobile phase consisting of methanol with 0.1% TFA (solvent A) and water with 0.1% TFA (solvent B). Gradient 1 [time/min](solvent A: solvent B): [0-2](50:50), [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17](95:5), [17][18][19][20][21][22](95:5), [22][23][24][25][26](50:50).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The analytical HPLC was performed on a Gemini® 5 µm C18 110 Å LC column 150×4.6 mm (Phenomenex) at a flow rate of 1 mL min -1 , with a mobile phase consisting of methanol with 0.1% TFA (solvent A) and water with 0.1% TFA (solvent B). Gradient 1 [time/min](solvent A: solvent B): [0-2](50:50), [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17](95:5), [17][18][19][20][21][22](95:5), [22][23][24][25][26](50:50).…”
Section: Methodsmentioning
confidence: 99%
“…18,19 In other studies, we and others have found that the use of the acids Ph2C(X)CO2H (X = OH, NH2) can impart high crystallinity in products and be beneficial for characterization. [20][21][22][23] Thus, herein we report our initial studies on rhenium complexes bearing ligands derived from diphenylglycine (X = NH2) and the related pro-ligand benzilic acid (X = OH).…”
Section: Introductionmentioning
confidence: 99%
“…4 A search of the CSD revealed 33 hits for the Ph 2 C(N)(CO 2 ) moiety, the majority of which were organic in nature; a chart of the non-organic structures is given in the ESI (Chart S1 †). 5 We have recently screened a number of these systems for the ROP of cyclic esters, in particular alkylaluminium species, 6 and a number of complexes comprising Li x O y rings and ladders 7 have revealed reasonable activity. Given that zinc complexes have also shown promise over the years as ROP pre-catalysts, 8 we have now turned our attention to alkylzinc complexes incorporating the Ph 2 C(X) motif.…”
Section: Introductionmentioning
confidence: 99%
“…We note that a number of lithium-containing cages, rings, and ladders, supported primarily by phenolate-type ligation, have previously been employed for the ROP of cyclic esters. 21 The use of calixarenes though, is somewhat limited. 4,22 …”
Section: Introductionmentioning
confidence: 99%